Shock-induced deformation twinning and softening in magnesium single crystals. (September 2020) - Flanagan, Tyler J.; Vijayan, Sriram; Galitskiy, Sergey; Davis, Jacob; Bedard, Benjamin A.; Williams, Cyril L.; Dongare, Avinash M.; Aindow, Mark; Lee, Seok-Woo
Abstract: Magnesium is widely regarded as an excellent structural material, primarily because it forms the basis for a range of light-weight high-strength alloys. Recently, high-strain rate deformation of magnesium has received a great deal of attention due to the complicated deformation modes that involve combinations of dislocation slip and deformation twinning. In this study, single crystal magnesium samples were shock-compressed along the c- and a-axis, then released back to ambient conditions. Post-mortem transmission electron microscopy revealed that extension twins developed for both c- and a-axis shock loading. Also, the nanoindentation hardness values for these shocked samples were compared to those for samples compressed under quasi-static conditions; it was found that the hardness decreased with increasing strain rate for both c- and a-axis loading. Molecular dynamics simulations were performed to elucidate the detailed mechanisms of deformation twinning in terms of inertial confinement of sample geometry and different stress relaxation speed between impact and lateral directions. The conversion from work-done to heat was discussed to explain the influence of shock-induced heating on the residual hardness. These results give new insights into the residual mechanical response in shock-compressed materials and may help to develop a more fundamental understanding of shock phenomena in metallic materials. Graphical abstract: Unlabelled Image Highlights: Samples of single crystal magnesium were shock-compressed and released along both the a- and c- axes. Extension twinning was observed using transmission electron microscopy. Shock-induced softening was observed using nano-indentation. Analytical model and molecular dynamics simulations were used to examine the evolution of pressure profiles and extension twinning during the shock-recovery process.